Kinerja Keuangan Berbasis Shari’ate Value Added Approach: Komparasi Antara Bank Umum Sharia dan Unit Usaha Sharia di Indonesia - Sri Wahyuni; Pujiharto Pujiharto (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP), 2017)
This study aims to measure the financial performance of Islamic banking in Indonesia using Sharia Value Added Approach. In specific, objectives of this study is comparing financial performance between Islamic banking (sharia commercial banking) and sharia busness unit that measure using shari’ate value added approach. The object of this study is islamic banking covers Islamic Banking and Sharia Business Unit, with research period is 2010-2015. Sample selection using purposive sampling mehod. Financial performance was measued in this study is Return on Asset (ROA), Return on Equity (ROE), Net Profit to Productive Asset (NPPA), and Net Profit Margin (NPM). The result of this study shows that financial performance of Islamic banking is healty. There are a significant difference of ROA, ROE, and NPPA between sharia commercial banking and sharia business unit that measure using income statement approach and using sharia value added statement approach. But, NPM is not. The result of this study provides a significant contribution to developing Sharia Enterprise Theory. For manager of Islamic banking, Bank Indonesia and Sharia Financial Standard Board, the result of study can used to create policies related to measurement of Islamic Banking performance.Keywords: financial performance, shari’ate value added approach, Islamic banking, sharia business unit